2018
DOI: 10.31983/link.v14i2.3706
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Dzikir Dan Murottal Untuk Mengurangi Kecemasan Pada Pre Eklampsia Ringan

Abstract: Kematian ibu masih menjadi masalah besar di negara berkembang. Tiga penyebab utama kematian ibu di Banyumas adalah preeklamsia. Pre-eklampsia adalah kumpulan gejala yang terjadi pada kehamilan, persalinan, postpartum yang terdiri dari hipertensi dan proteinuria. Studi tersebut mengatakan bahwa kecemasan berhubungan dengan preeklamsia. Penelitian ini menggunakan desain Pra-eksperimen Pretest-PostestControlGroup. Pengukuran faktor risiko (kecemasan) menggunakan kuesioner T-MAS (Taylor Manifest Anxiety Scale) Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
2
0
1
Order By: Relevance
“…The results of this study are in line with the research of Widiastuti et al who explained the effectiveness of the dhikr relaxation intervention with a Sig value of 0.0001 so that the anxiety score decreased significantly for pregnant women with mild pre-eclampsia (Widiastuti et al 2018). In addition, Niko's research also revealed that dhikr therapy has an influence on anxiety that occurs in pregnant women because it is able to provide a calm feeling with a Sig value of 0.001 (Niko 2018).…”
Section: The Influence Of the Need For Help Model Through Dhikr Thera...supporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study are in line with the research of Widiastuti et al who explained the effectiveness of the dhikr relaxation intervention with a Sig value of 0.0001 so that the anxiety score decreased significantly for pregnant women with mild pre-eclampsia (Widiastuti et al 2018). In addition, Niko's research also revealed that dhikr therapy has an influence on anxiety that occurs in pregnant women because it is able to provide a calm feeling with a Sig value of 0.001 (Niko 2018).…”
Section: The Influence Of the Need For Help Model Through Dhikr Thera...supporting
confidence: 91%
“…The results of this study are supported by research by Widiastuti et al, who said that dhikr relaxation was effective in reducing feelings of anxiety experienced by pregnant women with a diagnosis of mild pre-eclampsia (Widiastuti et al 2018). In addition, Rahman's research revealed that the anxiety level of pregnant women decreased after the dhikr stages were carried out which could generate thoughts and beliefs if all trials were able to be faced properly with the help of Allah SWT (Rahman 2020).…”
Section: Overview Of Anxiety Levels Against Baby Loss In Severe Pre-e...supporting
confidence: 83%
See 1 more Smart Citation
“…The cells of the body are influenced by acoustic frequencies (sound) which then affect the electromagnetic field of these cells. A study showed that one of the best efforts to reprogram the body's cells is reading Al-Quran in an authentic way [20]. The human voice, which is a wonderful healing instrument and the most accessible tool, is physically present in the recitation of Al-Quran.…”
Section: Discussionmentioning
confidence: 99%
“…Dan redemonstrasi memberikan pengalaman nyata sehingga membuat peserta semakin memahami dan menguasai ketrampilan. Merujuk pada kerucut pengalaman Edgar Dale, dimana responden yang melakukan aktivitas, bibir dan pikiran bekerja, hasilnya lebih baik dibanding dengan yang hanya mendengarkan [5].…”
Section: Gambar 2 Kegiatan Pelatihanunclassified